Biopolymer-based biomaterial containing gold nanoparticles-bioactive glass for bone regeneration in a complicated tibial fracture in a dog: a case report - Aștilean, Andreea Niculina; Dreancă, Alexandra; Ober, Ciprian; Oros, Nicușor Valentin; Peștean, Cosmin Petru; Mârza, Sorin Marian; Neagu, Daniela; Magyari, Klara; Gado, Cristina; Oana, Liviu (Frontiers in Veterinary Science, 2025)
A revision surgery for a tibial fracture in a dog, complicated by a secondary fracture site, implant migration, breakage, and bending of the initial implants, was described. After diaphyseal tibial osteotomy, the resulting gaps and bone defects were filled with the alginate–pullulan–bioactive glass–gold nanoparticles (Alg-Pll-BGAuSP) composite. The objective of applying this composite was to stimulate cell proliferation, based on its demonstrated bioactive effect, biodegradability, biocompatibility, and osteoinductive properties. The regenerative process was monitored both clinically and radiologically, with the aim of achieving an improved outcome and enhancing the welfare of the animal. At 12 weeks postoperatively, the implants were removed, and the limb resumed its original function. The application of this biomaterial enhanced the healing of a long bone defect, thereby promoting the formation of high-quality bone tissue in a relatively short time, despite the absence of anastomosis at the defect margins and the complexity of the case. Thus, the Alg-Pll-BGAuSP composite appears to be a viable treatment scaffold for further bone regeneration clinical trials. This first clinical report supports its potential as a scaffold for bone regeneration in complicated fractures.